PEMANFAATAN ARANG BATANG PISANG (Musa paradisiacal) UNTUK MENURUNKAN KESADAHAN AIR - Ni Made Shinta Megawati; Anak Agung Bawa Putra; James Sibarani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
The study about utilization of char made from banana (Musa paradisiacal) to reduce water hardness had been carried out. In this study, the surface area, equilibrium time of adsorption of metal ions, adsorption isotherm, capacity of adsorption, and the effect of pH on metal ions adsorption were used as parameters. Futher the optimum conditions were used to reduce the water hardness. The results of this study showed that the surface area, capacity of adsorption on Ca from 100 ppm solution were 3.3932 m2/g and 2.8112 mg/g respectively with equilibrium time of 90 minutes. Whereas, the capacity of adsorption on Mg2+from 75 ppm solution was 2.3371 mg/g with equilibrium time of 90 minutes. The adsorption capacity increased to the highest value at pH 7 which were 4.1197 mg/g and 3.0210 mg/g for Ca2+and Mg2+ respectively. The value of total hardness of water samples decreased by 63.057 mg/L in 4 hours contact time.